Dampak Paparan Logam Berat Besi (Fe) Terhadap Hemoglobin (Hb) Pada Darah Tikus Wistar - Dewi Yudiana Shinta; Muhammad Diki Juliandi; Def Primal (Pelantar Press, 2024)
Iron (Fe) heavy metal, in certain amounts is an essential heavy metal, much needed by living organisms; however, in excessive amounts, iron metal can be toxic. Iron (Fe) metal has adverse effects on health, as it is harmful to organs and causes physiological problems especially Hb levels in the blood. This study aims to see the impact of exposure to heavy metal iron (Fe) on living things represented by Wistar rats. The benefit of this study is to provide an overview of the exposure of living things, especially humans, will have an impact on hemoglobin levels that make humans can be affected by anemia. This research design with a post test group design only with a total sample of 10 rats divided into 3 groups, namely negative control, treatment 1 with a dose of 0.54 mg / BW and treatment 2 with a dose of 1.08 mg/BW, giving (Fe) is given from the first day to the 14th day and then taking rat blood through the orbital eye. Examination of heavy metal Fe with atomic absorption spectrophotometry and for Hb levels with Hemosmart Gold Hemoglobin Test Strip. The results of this study heavy metal (Fe) levels in the blood of rats are the highest levels found in the sample 1.08mg / BW T3 (H14) with Fe levels of 44.14 µg / L and the lowest Fe levels found in the sample with Fe levels of 14.78 µg / L and control of rats, Fe levels are 9.85 µg / L. Hb levels in the blood of rats were 0.54mg/BB dose was (7.4 g/dl 6.8g/dl), 1.08mg/BB dose obtained hemoglobin results (7.2g/dl 7.6g/dl). The normal Hb level of control rats in rat blood is 6.1 g/dL. The conclusion of this study is that the level of Fe that enters the body of rats greatly affects the hemoglobin (Hb) of wistar rats where if the level of heavy metal Fe increases in the blood there will be a decrease in hemoglobin (Hb) levels in the blood which will cause anemia.